Tanggung Jawab Orang Tua Terhadap Pendidikan Anak - Azizah Tulfauziah; Latifah Salsabila; Rani Sugiarti; Suci Amalia; Wismanto Wismanto (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
Children are a gift and a trust that Allah gives to His servants who will be responsible in the afterlife. As parents, we have an obligation to educate our children from an early age. Early childhood development is closely related to the environment and family. The aim of this research is to explain the responsibilities of parents in their children's education. This research uses qualitative research methods which are presented in an educational descriptive manner. The results of this research show that parents are the first place where children receive education in the family. A child's personality is initially formed in the family. Parents must have concepts and arrangements regarding their children's education, such as moral education, character education, science education, religious knowledge education, fair treatment of children, and giving love and care to children. Parents are role models for their children. Therefore, the role of parents in developing and shaping children's personalities from an early age is very important.